DAMPAK REVITALISASI PASAR TRADISIONAL TERHADAP KONDISI SOSIAL EKONOMI PEDAGANG SOUVENIR DI PASAR RAKYAT TEMATIK WISATA UBUD - I Wayan Sandika Putra; Ida Bagus Suryawan; Putri Kusuma Sanjiwani (CV. Lafadz Jaya, 2026)
The revitalization of the Ubud Thematic Tourism Public Market has brought physical, social, and economic changes that have affected the socio-economic conditions of souvenir traders. This study aims to describe these changes and analyze the impact of revitalization on the socio-economic conditions of souvenir traders. The research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. Data analysis follows the interactive model of Miles and Huberman, consisting of data collection, data reduction, data display, and conclusion drawing. The results show that revitalization has had a positive impact on traders’ educational conditions through the improvement of digital skills, including the use of QRIS and EDC payment systems and the adoption of basic bookkeeping practices. However, training related to foreign languages and digital marketing has not yet been provided. In terms of working conditions, revitalization has increased working hours, supported by improved efficiency, security, comfort, and work motivation. Nevertheless, social disparities have emerged between traders located on the first and second floors. Despite this, revitalization has also contributed positively by enhancing interaction and cooperation among traders. Regarding income conditions, the findings indicate that income improvements remain suboptimal or have even declined compared to the pre-COVID-19 period, mainly due to the increasing number of traders without product diversification and the less strategic access to the second floor.